Racial Disparities in Nutritional Risk and Its Association with Chronic Disease and Health Outcomes Among Community-Dwelling Older Adults in the Adult Day Health Setting (P04-121-19). (13th June 2019) - Sadarangani, Tina; Missaelides, Lydia; Brody, Abraham; Trinh-Shevrin, Chau
Abstract: Objectives: Adult day health centers (ADHCs) serve >260, 000 chronically ill individuals annually and are a preferred long-term care source for racial minorities, who also experience diet related disparities. Evidence regarding prevalence of nutritional risk is needed to inform dietary intervention planning in ADHCs. This study (1) identified prevalence of nutritional risk and associated factors, in a diverse sample of older ADHC users, (2) stratified differences in nutritional risk by race, and (3) explored associations between nutritional risk, chronic illness, and healthcare utilization. Methods: This was a secondary cross-sectional analysis of data originally collected by registered nurses between 2013–2017 at 12 California-based ADHCs. Nutritional risk was assessed using the DETERMINE checklist. Results were stratified by race to examine statistically significant ( P  < .05) differences among White Non-Hispanics, Blacks, Hispanics, and Asians aged > 50. Bivariate chi-square tests were used to explore associations between nutritional risk and chronic disease, as well as healthcare utilization. Results: The majority of the sample ( N  = 188) was at moderate (45.2%) or high (38.5%) nutritional risk, with statistically significant racial differences ( P  = .01). Blacks (65%) were at high nutritional risk compared to whites (39.5%), Hispanics (33.3%), and Asians (29.30%). Associations between nutritional risk and hypertension ( P  = .01), hyperlipidemia ( P  = .04), diabetes ( P  = .03), dementia ( P  = .00), depression ( P  = .01), and stroke ( P  = .04) and emergency department use ( P  = .01) were significant. Among blacks, 76.5% ate < 5 servings of fruits, vegetables, or milk daily, compared to 39.5% of whites; 21% of blacks ate <2 meals a day, compared to 2% of whites and Hispanics. Blacks (48.5%) more often reported involuntary weight loss/gain compared to whites (23.3%), and had the highest prevalence of tooth loss/mouth pain (41.2%) of any racial group. Conclusions: Older adults in ADHCs are at elevated risk of malnutrition, and blacks disproportionately so. Routine nutritional screening in ADHCs should be considered, but customized population specific approaches are needed to address unique drivers of malnutrition risk. Funding Sources: New York University Center for the Study of Asian American Health Pilot Project Program for Alzheimer's Disease & Thomas J. Long Foundation. Supporting Tables, Images and/or Graphs: